High Extracellular Levels of Mycobacterium tuberculosis Glutamine Synthetase and Superoxide Dismutase in Actively Growing Cultures Are Due to High Expression and Extracellular Stability Rather than to a Protein-Specific Export Mechanism - Tullius, Michael V. (American Society for Microbiology, 2001)
Glutamine synthetase (GS) and superoxide dismutase (SOD), large multimeric enzymes that are thought to play important roles in the pathogenicity of Mycobacterium tuberculosis, are among the bacterium's major culture filtrate proteins in actively growing cultures. Although these proteins lack a leader peptide, their presence in the extracellular medium during early stages of growth suggested that they might be actively secreted. To understand their mechanism of export, we cloned the homologous genes (glnA1 and sodA) from the rapid-growing, nonpathogenic Mycobacterium smegmatis, generated glnA1 and sodA mutants of M. smegmatis by allelic exchange, and quantitated expression and export of both mycobacterial and nonmycobacterial GSs and SODs in these mutants. We also quantitated expression and export of homologous and heterologous SODs from M. tuberculosis. When each of the genes was expressed from a multicopy plasmid, M. smegmatis exported comparable proportions of both the M. tuberculosis and M. smegmatis GSs (in the glnA1 strain) or SODs (in the sodA strain), in contrast to previous observations in wild-type strains. Surprisingly, recombinant M. smegmatis and M. tuberculosis strains even exported nonmycobacterial SODs. To determine the extent to which export of these large, leaderless proteins is expression dependent, we constructed a recombinant M. tuberculosis strain expressing green fluorescent protein (GFP) at high levels and a recombinant M. smegmatis strain coexpressing the M. smegmatis GS, M. smegmatis SOD, and M. tuberculosis BfrB (bacterioferritin) at high levels. The recombinant M. tuberculosis strain exported GFP even in early stages of growth and at proportions very similar to those of the endogenous M. tuberculosis GS and SOD. Similarly, the recombinant M. smegmatis strain exported bacterioferritin, a large (∼500-kDa), leaderless, multimeric protein, in proportions comparable to GS and SOD. In contrast, high-level expression of the large, leaderless, multimeric protein malate dehydrogenase did not lead to extracellular accumulation because the protein was highly unstable extracellularly. These findings indicate that, contrary to expectations, export of M. tuberculosis GS and SOD in actively growing cultures is not due to a protein-specific export mechanism, but rather to bacterial leakage or autolysis, and that the extracellular abundance of these enzymes is simply due to their high level of expression and extracellular stability. The same determinants likely explain the presence of other leaderless proteins in the extracellular medium of actively growing M. tuberculosis cultures.